The use of animals in circuses and shows in Denmark, Sweden, Norway and Finland - Sacha Lucassen (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
In recent years, the use of (wild) animals in circuses, and similar performances, has become the subject of much public and political debate throughout the world. This has led, especially over the last decade, to a number of countries adopting regulations concerning the use and displaying of (wild) animals in circuses and shows. This article investigates what regulations Denmark, Sweden, Norway and Finland have adopted concerning the use of (wild) animals in shows. These countries limit the use of (wild) animals, but do not completely prevent it. Norway has published a positive list of animals who are allowed for use, both Finland and Sweden have adopted a negative list of animals, which are banned in all circumstances, and Denmark has approved a positive as well as a negative list of animals.